2015
DOI: 10.1292/jvms.15-0280
|View full text |Cite
|
Sign up to set email alerts
|

Effect of methotrexate on rostral migratory stream in newborn rats

Abstract: Two-day-old rats were treated with subcutaneous injections of methotrexate (MTX) 5 mg/kg and 150 mg/kg, and their rostral migratory streams (RMS) were examined time-dependently. MTX treatment increased pyknotic and TUNEL-positive cells and decreased mitotic and phospho-Histone H3-positive cells at almost all time points in the vertical arm, elbow and horizontal arm regions of the RMS. There were more TUNEL-positive cells ratio in the MTX 150 mg/kg group than in the MTX 5 mg/kg group. Treatment with MTX 150 mg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
(43 reference statements)
0
2
0
Order By: Relevance
“…These data suggested that the SVZ, lining the walls of the lateral ventricles, is sensitive to exogenous toxicants, and subsequently may constitute the real “window of the brain” as proposed by many authors (Gross and Weindl, 1987 ; Moyse et al, 2006 ; Joly et al, 2007 ; Lin et al, 2015 ). Such an assumption is reinforced by a recent study showing that perinatal exposure to another environmental toxicant, methotrexate, also led to SVZ alterations (Hirako et al, 2016 ). These aversive effects of exogenous compounds on the SVZ could be inherent to its intrinsic structure characterized by permeable fenestrated capillaries and thus a lack of endothelial blood–brain-barrier (BBB) (Johnson and Gross, 1993 ; Tavazoie et al, 2008 ).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…These data suggested that the SVZ, lining the walls of the lateral ventricles, is sensitive to exogenous toxicants, and subsequently may constitute the real “window of the brain” as proposed by many authors (Gross and Weindl, 1987 ; Moyse et al, 2006 ; Joly et al, 2007 ; Lin et al, 2015 ). Such an assumption is reinforced by a recent study showing that perinatal exposure to another environmental toxicant, methotrexate, also led to SVZ alterations (Hirako et al, 2016 ). These aversive effects of exogenous compounds on the SVZ could be inherent to its intrinsic structure characterized by permeable fenestrated capillaries and thus a lack of endothelial blood–brain-barrier (BBB) (Johnson and Gross, 1993 ; Tavazoie et al, 2008 ).…”
Section: Discussionmentioning
confidence: 95%
“…In line with this, Autism Spectrum Disorders (ASD) are thought to be associated with alterations in neonatal neurogenesis in the SVZ (Kotagiri et al, 2014 ). Indeed, it was shown that neurobehavioral defects concomitant to cellular SVZ abnormalities were induced by perinatal exposure to methotrexate (Seigers et al, 2015 ; Hirako et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%